Let be a circle with radius . Let be any point on and let be the tangent to at point . Let and be points of on opposite sides of such that and . Let be any point of different from . Find the value of:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Without loss of generality let r be a unit (rescaling does not change trigonometric ratios) and let us introduce coordinates, such that the centre of Γ = ( 0 , 0 ) , and A = ( 1 , 0 ) . Then we have B = ( 1 , − 1 2 ) , C = ( 1 , 2 4 ) .
P lies on the unit circle, so if its coordinates are ( − x , − y ) , then x 2 + y 2 = 0 .
P B = ( x + 1 , y − 1 2 ) ; P A = ( x + 1 , y ) and P C = ( x + 1 , y + 2 4 ) .
cos ∠ A P B = ∣ P B ∣ × ∣ P A ∣ P B ⋅ P A = d ( x + 1 ) 2 + y ( y − 1 2 ) , where
d = ( ( x + 1 ) 2 + ( y − 1 2 ) 2 ) ( ( x + 1 ) 2 + y 2 ) =
= ( x + 1 ) 4 + ( x + 1 ) 2 ( y 2 + ( y − 1 2 ) 2 ) + y 2 ( y − 1 2 ) 2 .
Now cos 2 ∠ A P B = d 2 ( x + 1 ) 4 + y 2 ( y − 1 2 ) 2 + 2 ( x + 1 ) 2 y ( y − 1 2 ) , so
sin 2 ∠ A P B = 1 − cos 2 ∠ A P B =
= d 2 d 2 − ( x + 1 ) 4 − y 2 ( y − 1 2 ) 2 − 2 ( x + 1 ) 2 y ( y − 1 2 ) =
= d 2 ( x + 1 ) 2 ( y 2 + ( y − 1 2 ) 2 − 2 y ( y − 1 2 ) ) =
= d 2 ( x + 1 ) 2 ( y − ( y − 1 2 ) ) 2 = d 2 1 4 4 ( x + 1 ) 2 ,
hence sin ∠ A P B = d 1 2 ( x + 1 ) and so
cot ∠ A P B = sin ∠ A P B cos ∠ A P B = 1 2 ( x + 1 ) ( x + 1 ) 2 + y ( y − 1 2 ) .
Analogically (replacing -12 by 24 everywhere), we see that
cot ∠ A P C = 2 4 ( x + 1 ) ( x + 1 ) 2 + y ( y + 2 4 ) .
Hence the fraction in questions is equal to:
( 2 4 ( x + 1 ) ( x + 1 ) 2 + y ( y + 2 4 ) + 1 2 ( x + 1 ) ( x + 1 ) 2 + y ( y − 1 2 ) ) − 1 =
= ( 2 4 ( x + 1 ) ( ( x + 1 ) 2 + y ( y + 2 4 ) + 2 ( x + 1 ) 2 + 2 y ( y − 1 2 ) ) − 1 =
= 3 x 2 + 3 y 2 + 6 x + 3 2 4 ( x + 1 ) .
Note that x 2 + y 2 = 1 as P lies on the unit circle, hence the expression above is:
3 + 6 x + 3 2 4 ( x + 1 ) = 6 ( x + 1 ) 2 4 ( x + 1 ) = 4 .